Chelsea, Butler County - Morris, Brooke (Kansas State University, The Chapman Center for Rural Studies, 2013)
Chelsea was located in chelsea Township of Butler County from 1857-1978. This study includes early maps of the county, information provided by the Butler County Historical Society, and some photographs of the town before it was gone. This analysis shows the persistence that the people of this small community had to save their beloved town.
Brooke Morris, “Chelsea, Butler County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/129.
Keywords: Butler County; Chelsea Township; El Dorado; George T. Donaldson; New Chelsea; South Chelsea